Inconspicuous Nasoethmoidal Encephalocele Might Be Wrongly Diagnosed - Weng, Jun Tang; Wan Sulaiman, Wan Azman (The Korean Society of Plastic and Reconstructive Surgeons, 2016)
We have read the paper of Song et al. [1] on frontonasal dysplasia deformity. It was an interesting discussion of an image that depicts a boy with a nose deformity, and it was reported that no basal encephalocele was observed. We would like to point out that we had a similar case of a girl with the same nose deformity. As in the report by Song et al., our patient also presented with mild hypertelorism, a broad nasal root and a bifid nasal tip (Fig. 1). The defect at the nasal dorsum had never increased in size and was not cystic. Her parents were anxious about the cosmetic appearance of their child and requested an early excision of the nasal defect and rhinoplasty.